Organizing a COVID-19 triage unit: a Swiss perspective. Issue 1 (1st January 2020) - Peros, Georgios; Gronki, Ferda; Molitor, Nadine; Streit, Michael; Sugimoto, Kiyoshi; Karrer, Urs; Lunger, Fabian; Adamina, Michel; Breitenstein, Stefan; Lamdark, Tenzin
ABSTRACT: Background: With the rapid global spread of the acute respiratory syndrome coronavirus 2, urgent health-care measures have been implemented. We describe the organizational process in setting up a coronavirus disease 2019 triage unit in a Swiss tertiary care hospital. Methods: Our triage unit was set-up outside of the main hospital building and consists of three areas: 1. Pre-triage, 2. Triage, and 3. Triage plus . The Pre-triage check-points identify any potential COVID-19-infected patients and re-direct them to the main Triage area where trained medical staff screen which patients undergo diagnostic testing. If testing is indicated, nasopharyngeal swabs are performed. If patients require further investigations, they are referred to Triage plus . At this stage, patients are then discharged home after additional testing or admitted to the hospital for management. Observations: A total of 1265 patients were screened between 10 March 2020 and 12 April 2020 at our Triage unit. Of these, 112 (8.9%) tested positive. 73 (65%) of the positively-tested patients were female and 39 (35%) were male. The mean age for all patients was 43.8 years (SD 16.3 years). Distinguishing between genders, mean age for females was 41.1 (SD 16.5) and mean age for males was 48.6 (SD 14.9), with females being significantly younger than males ( p  < 0.001). Conclusion: Our triage unit was set-up as part of a large-scale restructuring process. Current challenges include low sensitivity for test results as well as limited staff and resources. We hope that our experience will help other health care institutions develop similar triage systems.